Dynamic Stimulation of Visual Cortex Produces Form Vision in Sighted and Blind Humans - Beauchamp, Michael S.; Oswalt, Denise; Sun, Ping; Foster, Brett L.; Magnotti, John F.; Niketeghad, Soroush; Pouratian, Nader; Bosking, William H.; Yoshor, Daniel (Cell, 2020)
A visual cortical prosthesis (VCP) has long been proposed as a strategy for restoring useful vision to the blind, under the assumption that visual percepts of small spots of light produced with electrical stimulation of visual cortex (phosphenes) will combine into coherent percepts of visual forms, like pixels on a video screen. We tested an alternative strategy in which shapes were traced on the surface of visual cortex by stimulating electrodes in dynamic sequence. In both sighted and blind participants, dynamic stimulation enabled accurate recognition of letter shapes predicted by the brain’s spatial map of the visual world. Forms were presented and recognized rapidly by blind participants, up to 86 forms per minute. These findings demonstrate that a brain prosthetic can produce coherent percepts of visual forms. [Display omitted] •Visual cortical prosthetic stimulation paradigms were examined•Letters or other shapes were traced on the surface of cortex with electrical current•Static stimulation was unable to produce letter percepts in participants•Dynamic current steering evoked percepts of letter forms by blind and sighted participants Dynamic stimulation of visual cortex allows both sighted and blind subjects to recognize a variety of letter shapes without training and with high accuracy.